Dual-modal fullerenol probe containing glypican-3 monoclonal antibody for electron paramagnetic resonance/fluorescence imaging. Issue 4 (3rd April 2021) - Zhu, Yun-Lu; Shen, Yan-Chun; Liu, Fan; Chen, Si; Yan, Guo-Ping; Liang, Shu-Cai; Zhang, Yun-Fei; Wu, Yan-Guang
Abstract: The multi-modal imaging contrast agent has been attracted an increased interest to the tumor detecting and diagnosis in these recent years since the multi-modal imaging technology combines the advantages of several medical imaging modalities. A water-soluble fullerenol probe containing glypican-3 monoclonal antibody (GPC3-mAb) group mAb-GPC3-C60 (OH)10 -(TMIO)3 -(NI)3 was synthesized by the incorporation of 5-formyl-1, 1, 3, 3-tetramethylisoindolin-2-yloxyl (FTMIO), naphthalimide (NI) and GPC3-mAb as a tumor-targeting group into fullerenol C60 (OH)11 . This nanomaterial was further characterized by FTIR, UV, MS, fluorescence, etc., and then its properties including electron paramagnetic resonance (EPR), particle size, electrophoresis, electrochemical assay, cell cytotoxicity, cell uptake and fluorescent imaging of HeLa tumor cells in vitro were also evaluated. Experiment results indicated that mAb-GPC3-C60 (OH)10 -(TMIO)3 -(NI)3 had similar fluorescent properties as NI and similar electrochemical and redox properties as 5-carboxy-1, 1, 3, 3-tetramethylisoindolin-2-yloxyl (CTMIO). Moreover, mAb-GPC3-C60 (OH)10 -(TMIO)3 -(NI)3 possessed low cell cytotoxicity, good fluorescence and good tumor-targeting property. Meanwhile, mAb-GPC3-C60 (OH)10 -(TMIO)3 -(NI)3 can be taken up highly by HeLa tumor cells, achieve good green fluorescent imaging in tumor cells and highly enhance the contrast of fluorescent images. Therefore, mAb-GPC3-C60 (OH)10 -(TMIO)3 -(NI)3 can disperse homogeneously in aqueous solution and be used as a potential tumor-targeting dual-modal contrast agent for EPR imaging/fluorescence imaging (EPRI/FI).